Synthesis and Properties of Acridine and Acridinium Dye Functionalized Bis(terpyridine) Ruthenium(II) Complexes. Issue 20 (29th May 2018) - Eberhard, Jens; Peuntinger, Katrin; Fröhlich, Roland; Guldi, Dirk M.; Mattay, Jochen
Abstract : We present first principle studies on the rational design of an acridine/ N ‐methylacridinium dye (Acr/MeAcr + ) substituted terpyridine ligand to investigate if these chromophores can act as triplet‐energy storage units in bis(terpyridine) ruthenium(II) complexes. We studied the influence of the dye form (Acr/MeAcr + ) as well as the interconnecting linker unit (none, 4‐phenyl, or 5‐thien‐2‐yl) and investigated these aspects by steady‐state/time‐resolved spectroscopy, cyclic voltammetry, X‐ray structure analysis, and DFT calculations. Abstract : This publication describes a rationally designed class of acridine/ N ‐methylacridinium dye (Acr/MeAcr + ) substituted terpyridine ligands in order to investigate if these chromophores can act as triplet‐energy storage units in bis(terpyridine) ruthenium(II) complexes.